Religious coping and caregiver well-being in Mexican-American families - Herrera, Angelica P. (Aging Ment Health, 2009)
OBJECTIVE: We sought to explore the association of religious and spiritual coping with multiple measures of well-being in Latinos caring for older relatives with long-term or permanent disability, either with or without dementia. METHODS: Using a multi-dimensional survey instrument, we conducted in-home interviews with 66 predominantly Mexican-American Catholic family caregivers near the US–Mexico border. We assessed caregivers' intrinsic, organizational and non-organizational religiosity with the Duke Religiosity Index, as well as Pargament's brief positive and negative spiritual coping scale to determine the association of religiosity with caregivers' mental and physical health, depressive symptomatology and perceived burden. RESULTS: Using regression analysis, we controlled for sociocultural factors (e.g. familism, acculturation), other forms of formal and informal support, care recipients' functional status and characteristics of the caregiving dyad. Intrinsic and organizational religiosity was associated with lower perceived burden, while non-organizational religiosity was associated with poorer mental health. Negative religious coping (e.g. feelings that the caregiver burden is a punishment) predicted greater depression. CONCLUSION: Measures of well-being should be evaluated in relation to specific styles of religious and spiritual coping, given our range of findings. Further investigation is warranted regarding how knowledge of the positive and negative associations between religiosity and caregiving may assist healthcare providers in supporting Latino caregivers.